A Cross-sectional Study on Patients' Perspective Towards Dermatology Outpatient Services from a Tertiary Care Center in Nepal - Pandey, Prajwal; Shah, Raju; Rani, Swati (Nepal Journal of Dermatology, Venereology & Leprology, 2024)
Introduction: Patient-centered care has received greater prominence in recent years, and it is paramount to assess the patient’s satisfaction to improve the quality of healthcare services. The present study is aimed at understanding the patients’ perspectives regarding dermatology outpatient services offered at a tertiary care center to determine the areas for improvement for better patient satisfaction. Objective: This study is intended to understand the patients’ perspectives regarding a typical dermatology OPD setup and to identify the areas for improvement in a tertiary center in Nepal. Materials and Methods: The descriptive cross-sectional study was carried out using a content-validated, pre-tested, standardized, and translated questionnaire. All the patients who visited the outpatient department of Dermatology tertiary care center during the month of April 2022 and were willing to participate in the study were included. Result: A total of 157 patients participated in the survey. The majority of the participants were males (56.7%) and belonged to urban domiciles (80.9%). Nearly 42% of the subjects were seeking dermatology consultation for the first time, and 68.2% responded that the duration of consultation was sufficient. The details of symptoms, clinical results, and medication were clearly understood by 89.8%, 82.2%, and 73.9% of the subjects, respectively. Maintenance of privacy was reported by 76.4% of the participants. However, 25.5% of the subjects reported a waiting time of ≥4 hours for consultation, and 34.4% suggested the need for more manpower. Conclusion: The majority of the patients had a high degree of satisfaction. The areas of improvement include the adoption of technology-based appointment booking system, ensuring a good waiting ambience, increasing manpower, and reducing waiting time for consultations.